Realistic Mathematics Education (RME) Sebagai Sebuah Pendekatan pada Pengembangan Modul Matematika Berbasis Teori Multiple Intelligences Howard Gardner - Faidah, Nuzulul; Masykur, Ruhban; Andriani, Siska; Haerlina, Lina (Universitas Islam Negeri Raden Intan Lampung, 2019)
Abstract: This study aims to develop modules based on the Multiple Intelligences Theory of Howard Gardner using the Realistic Mathematics Education (RME) approach in class VIII Middle School. This research is an R and D research which stages using the development of Borg and Gall. The instrument used in this study uses a questionnaire given to material experts and media experts to test the feasibility of this module. The research results that have been developed are feasible to be used in proper learning are used seen from the results of the validation of material experts and media experts. On the results of the media expert test obtained an average of 80% with the Criteria